Izquierda, trabajadores y orden oligárquico, 1880-1900 - Roy Hora (Centre de Recherches sur les Mondes Américains, 2020)
Studies on the origins of the Argentine labor movement argue that the late nineteenth century working class faced exclusion and high levels of repression. The growing influence of Anarchist and Socialist agitators within the nascent unions, it is said, was a response to reactionary governing elites and harsh, abusive forms of capitalism. Based on the study of the most significant labor conflicts, protests and public rallies of the 1880-1900 period, this essay suggest that this approach requires revision. It shows that Argentina’s liberal political framework played an important role in channeling the workers’ collective action. Furthermore, it suggests that both government and opposition, as well as the press, regarded strikes and mobilization as legitimate means to further labor’s interests. In sum, workers’ demands were negotiated through, not against, the institutional forms of Argentina’s liberal, capitalist republic. Integration into the political order, rather than resistance, was the most significant aspect of worker’s politics.